Validation of Modelflow Estimates of Cardiac Output in Hemodialysis Patients. Issue 4 (10th January 2018) - MacEwen, Clare; Sutherland, Sheera; Daly, Jonathan; Pugh, Christopher; Tarassenko, Lionel
Abstract: Volume‐clamp technology (e.g. Finometer) has become a popular method of collecting continuous, non‐invasive, hemodynamic information during hemodialysis. There is minimal data validating the technique in this patient group. A gold standard cardiac output measurement can be obtained using ultrasound dilution in patients with arterio‐venous fistulae. Continuous cardiac output was measured in 124 hemodialysis sessions in 27 patients using a volume‐clamp device (Finometer PRO). Ultrasound dilution measurement was first taken at baseline (Transonic HD03), then used to calibrate the Finometer. Ultrasound dilution measurement was repeated 2 h into hemodialysis to assess drift following calibration. Pearson's correlation and Bland–Altman statistics, modified for repeated measures, were used to assess agreement between methods. Linear mixed models were constructed to identify factors that could explain session‐level and patient‐level variation in agreement. For baseline cardiac output before calibration, agreement between volume‐clamp and ultrasound dilution measurements was poor, at 25 ± 75% (correlation 0.26, P < 0.001). There was significant variation in agreement between patients, with age, peripheral vascular disease and hemodialysis vintage contributing to poorer agreement. For cardiac output 2 h after calibration, agreement was −5.2 ± 57.5% (correlation 0.6, P < 0.001). Dynamic changes in blood pressure and fluid balance during hemodialysis resulted in greater drift over time after calibration. There was a large error, both random and systematic, in volume‐clamp estimates of absolute, pre‐calibration cardiac output in this prevalent hemodialysis population. There was minimal bias and reasonable correlation for cardiac output 2 h post‐calibration, but limits of agreement remained too wide to meet current clinical standards.